2022
DOI: 10.1093/jas/skac058
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone promotes follicle development through activating the SIRT1/PGC-1α signaling pathway in the ovaries of weaned gilts

Abstract: This study aimed to investigate the effect of zearalenone (ZEA) exposure on follicular development in weaned gilts, and its mechanism based on the silent information regulator 1 (SIRT1)/peroxisome proliferator-activated receptor-γ co-activator 1α (PGC-1α) signaling pathway. Thirty-two healthy female weaned piglets (Landrace × Yorkshire × Duroc) with an average body weight of 12.39 ± 0.24 kg were randomly allotted to a basal diet supplemented with 0, 0.15, 1.5, or 3.0 mg/kg ZEA for a 32-d feeding test. Blood an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…However, a previous study showed that the positive detection rate of ZEN could reach 69.15%, and the highest value of ZEN in compound feed samples was 4.33 mg/kg [ 6 ]. In our study, significantly increased serum ZEN, α-ZOL, and β-ZOL levels of weaned piglets were observed in the piglets fed the diet containing 3.0 mg/kg ZEN, which was in line with our previous study [ 25 ]. Zhang et al [ 24 ] found that 970 μg/kg ZEN could increase the levels of ZEN, α-ZOL, and β-ZOL of serum in gilts.…”
Section: Discussionsupporting
confidence: 93%
“…However, a previous study showed that the positive detection rate of ZEN could reach 69.15%, and the highest value of ZEN in compound feed samples was 4.33 mg/kg [ 6 ]. In our study, significantly increased serum ZEN, α-ZOL, and β-ZOL levels of weaned piglets were observed in the piglets fed the diet containing 3.0 mg/kg ZEN, which was in line with our previous study [ 25 ]. Zhang et al [ 24 ] found that 970 μg/kg ZEN could increase the levels of ZEN, α-ZOL, and β-ZOL of serum in gilts.…”
Section: Discussionsupporting
confidence: 93%
“…With the increase of ZEA (0.5, 1 and 1.5 mg/kg), the ovarian size increased first and then decreased [ 42 ]. Wan et al [ 43 ] observed the increased quantity of atretic growing follicles, but a greater volume and quantity of healthy growing follicles in the deep ovarian cortex with an increasing level of dietary ZEA (0, 0.15, 1.5 and 3.0 mg/kg). The absence of a difference in estradiol and progesterone in this study might be attributed to that the estradiol and progesterone secreted by healthy growing follicles in the deep ovarian cortex could offset the insufficient secretion of atretic growing follicles.…”
Section: Discussionmentioning
confidence: 99%
“…ZEA, α-ZOL, and β-ZOL were detected in serum after pre-pubertal gilts were fed ZEA at doses of 5, 10 and 15 μg /kg BW for 21 and 42 days [ 48 ]. The contents of ZEA, α-ZOL, and β-ZOL in serum of ZEA treatment pigs (doses at 0.15, 1.5 and 3 mg/kg) were higher than those in control pigs [ 43 ]. Zöllner et al [ 44 ] reported that ZEA and its metabolites (α-ZOL and β-ZOL) were detected in urine, muscle tissue and liver of pigs after feeding them mycotoxin-contaminated oats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations